Native Borderland Children in the Belgian-German and Polish-German Borderlands. Comparing Verification and Nationalisation Narratives After the Second World War - Venken, Machteld (No Neighbors' Lands in Postwar Europe. Vanishing Others, 2023)
Keywords: Belgien; Deutschland; Kind; Nationalbewusstsein; Polen

Peripheries at the centre. Borderland schooling in interwar Europe - Venken, Machteld (Studies in contemporary European history, 2021)
Aus dem Verlagstext: „Following the Treaty of Versailles, European nation-states were faced with the challenge of instilling national loyalty in their new borderlands, in which fellow citizens often differed dramatically from one another along religious, linguistic, cultural, or ethnic lines. Peripheries at the Centre compares the experiences of schooling in Upper Silesia in Poland and Eupen, Sankt Vith, and Malmedy in Belgium — border regions detached from the German Empire after the First World War. It demonstrates how newly configured countries envisioned borderland schools and language learning as tools for realizing the imagined peaceful Europe that underscored the political geography of the interwar period.“
Keywords: Belgien; Bildungswesen; Deutschland; Eupen-Malmedy; Polen; Schule; Schulpolitik; Sprachpolitik

Cross-border everyday lives on the Luxembourg border? An empirical approach. The example of cross-border commuters and residential migrants - Wille, Christian; Roos, Ursula (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Alltag; Belgien; Deutschland; Frankreich; Grenzarbeitnehmer; Grenzgebiet; Luxemburg; Pendler; Regionale Mobilität